Customer Perceived Value (CPV) From The MPI Perspective: Integration of Academic Service Quality and Blessing Orientation - Siti Khofsah; Unzilah Khumairotusshiyamah; Muhammad Thoiful Abrar Thoiful Abrar; Muhammad Kholilurrohman; Zakyl Mustofa; Ida Kusumawati; Najiburrohman Najiburrohman (AFKARINA: Jurnal Pendidikan Agama Islam, 2024)
This study aims to analyze the digital content utilization strategy at Madrasah as an effort to modernize and increase the competitiveness of the educational institution. Using a qualitative approach through observation, documentation analysis, and in-depth interviews, this study explores the process of planning, producing, and distributing content across various digital platforms. The results show that the digital content strategy is implemented systematically through collaborative coordination meetings and content curation that combines religious identity with digital trends. Optimizing social media platforms and websites has proven effective in expanding the reach of information and changing public perception of the madrasah from a conventional one to a more modern, transparent, and competitive institution. In addition to the external impact of strengthening the image and trust of parents, this study also found a significant internal impact, namely increasing teachers' digital literacy, which has positive implications for the quality of classroom teaching. In conclusion, targeted digital content management is a strategic necessity for madrasahs to maintain relevance and competitive advantage amidst the dynamics of competition in today's educational institutions.